THE EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO, AND TOTAL ASSETS TURN OVER ON RETURN ON EQUITY WITH COMPANY SIZE AS A MODERATION VARIABLE: Studies in Automotive and Components Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2013-2020 Period - Nurul Izmi Aulia Zannati; Wajib Ginting (Journal of Accounting Inaba, 2022)
This study aims to examine the Current Ratio, Debt to Equity Ratio and Total Assets Turn Over to the Return On Equity with Firm Size as a Moderating Variable (Case Study on the Automotive and Components Sub-Sector listed on the Indonesia Stock Exchange in 2013-2020. The object of this research is Effect of Current Ratio, Debt to Equity Ratio and Total Assets Turn Over as Independent Variables, Return On Equity as Dependent Variables, and Firm Size as Moderating Variables. Based on the results of the research on the t test, the Current Ratio has no effect on the Return On Equity.Based on the results of the research on the t test, the Current Ratio has no effect on the Return On Equity of 1,825 < 1,681. Debt to Equity Ratio has no effect on the Return On Equity -6.579 < 1,681. Total Assets Turn Over has a affects on the Return On Equity 3,700 > 1,681. Firm size can moderate the effect of the Current Ratio on the Return On Equity of 1,815 > 1,681 with a significance level of 0,077 > 0,05. Firm size can moderate the effect of Debt to Equity Ratio on the Return On Equity of 6,559 > 1,661with a significance level of 0,000 > 0,05. Firm size cannot moderate the effect of Total Assets Turn Over on Return On Equity --2,924<1,661 with a significance level of 0,006 < 0,05. Based on the research of the f test, Current Ratio, Debt to Equity Ratio and Total Assets Turn Over simultaneously or together have a significant influence on the Return On Equity of 29,499 > 2.816. Current Ratio, Debt to Equity Ratio, and Total Assets Turn Over with Firm Size simultaneously or together have a significant influence on the Return On Equity of 39,150 > 2,330.